2016
DOI: 10.1016/j.mam.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of HIF in immunity and inflammation

Abstract: Uncontrolled or non-resolving inflammation underpins a range of disease states including rheumatoid arthritis, inflammatory bowel disease and atherosclerosis. Hypoxia is a prominent feature of chronically inflamed tissues. This is due to elevated oxygen consumption by highly metabolically active inflamed resident cells and activated infiltrating immunocytes, as well as diminished oxygen supply due to vascular dysfunction. Tissue hypoxia can have a significant impact upon inflammatory signaling pathways in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 79 publications
2
94
0
2
Order By: Relevance
“…HIF has cell type-specific roles, which have a profound impact on immune cell gene expression and downstream effector function. The specific functions of HIF in individual immune cell types has been recently reviewed and will be discussed only briefly here (reviewed in REFS 11,12). In neutrophils, HIF has a key role in the regulation of lifespan, antimicrobial peptide production and apoptosis 47,48 .…”
Section: Hif Modulation Of Immune Cell Functionmentioning
confidence: 99%
“…HIF has cell type-specific roles, which have a profound impact on immune cell gene expression and downstream effector function. The specific functions of HIF in individual immune cell types has been recently reviewed and will be discussed only briefly here (reviewed in REFS 11,12). In neutrophils, HIF has a key role in the regulation of lifespan, antimicrobial peptide production and apoptosis 47,48 .…”
Section: Hif Modulation Of Immune Cell Functionmentioning
confidence: 99%
“…Both inflammation and cancer are metabolically costly processes, which require increased oxygen consumption. In conjunction with some vascular dysfunction, it predisposes tissue to hypoxia and further activation of hypoxia-inducible transcription factors (HIF)s. Cross-talk between NF-ÎșB and HIFs attracts more attention nowadays [93,94]. …”
Section: Pro-inflammatory Mediators and Growth Factors In The Gastmentioning
confidence: 99%
“…A dominant and consistent theme that has evolved is that HIFs play a central role in the regulation of immune cell development and function; consequently, HIFs should be considered key regulators of immunity and inflammation. These studies revealed cell type-specific roles for HIF in the regulation of a number of processes central to immune cell activity (27). While our understanding of the role of HIFs in immune cell function is expanding, it is notable that during inflammation, hypoxia occurs not in isolation but in the complex milieu of the inflammatory lesion.…”
Section: Hif and Barrier Functionmentioning
confidence: 99%
“…Because of the role of hydroxylases in the regulation of hypoxia-responsive transcription factors, these enzymes also play a key role in the regulation of immune cell activity (27). While our understanding of the role of HIF hydroxylases in the regulation of immune cell function is far from complete, recent studies investigating individual HIF hydroxylase isoforms in discreet immune and epithelial cell subtypes have identified isoform-specific roles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89).…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%